Land use differentially affects fungal communities and network complexity in northeast China - Xu, Yanxia; Yang, Zhao; Wang, Xiaolong; Chai, Hua; Li, Shasha; Wu, Yue; Wang, Ruoding (Frontiers in Microbiology, 2022)
Background The soil fungal community is one of the most important drivers of the soil nutrient cycling that sustains plant growth. However, little research has been done on the effects of different land uses on soil fungal communities in northeast China. Methods In this study, we conducted a field experiment to investigate the effects of continuous cropping of grass, maize, and alfalfa on their respective fungal communities and co-occurrence networks. Results We showed that the physicochemical properties of the soil, such as nitrate (NO3-N), available phosphorus, and soil pH, were the most important driving factors affecting the structure of the soil fungal community in different cropping systems. In addition, compared to the cultivation of grass and maize, the continuous cropping of alfalfa increased the abundance of several beneficial as well as pathogenic species, such as Mortierella and Gaiellales. In addition, the networks differed among plant species and according to the number of years of continuous cultivation. Conclusion This suggests that the continuous cropping of alfalfa results in greater cooperation among fungi, which may be beneficial to the soil as well as to the development of the alfalfa.